2010
DOI: 10.1071/wf08109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fire severity on long-term occupancy of burned boreal conifer forests by saproxylic insects and wood-foraging birds

Abstract: Fire severity can vary greatly within and among burns, even in the Canadian boreal forest where fire regimes consist mostly of stand-replacing fires. We investigated the effects of fire severity on the long-term occupancy of burns by (i) saproxylic insects and (ii) three wood-foraging birds. Based on observations made 6 to 11 years after fire in burned conifer forests that varied in fire severity in Quebec, Canada, our results indicate that low-severity portions of the burns likely provided snag conditions sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 50 publications
1
34
2
Order By: Relevance
“…Because fire ages in our sample were from a single sampling season, it is impossible to say whether this pattern is pervasive or simply a reflection of characteristics of fires that burned in those particular years. Others have, however, also shown the species to remain fairly common 6-8 years post-fire (Hoyt andHannon 2002, Nappi et al 2010), and within-fire heterogeneity in fire severity may create conditions that promote a steady supply of dying trees, diverse prey resources, and habitat longevity extending beyond the first few years post-fire (Nappi et al 2010).…”
Section: Occupancy Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because fire ages in our sample were from a single sampling season, it is impossible to say whether this pattern is pervasive or simply a reflection of characteristics of fires that burned in those particular years. Others have, however, also shown the species to remain fairly common 6-8 years post-fire (Hoyt andHannon 2002, Nappi et al 2010), and within-fire heterogeneity in fire severity may create conditions that promote a steady supply of dying trees, diverse prey resources, and habitat longevity extending beyond the first few years post-fire (Nappi et al 2010).…”
Section: Occupancy Modelingmentioning
confidence: 99%
“…However, the species may also respond positively to lower intensity fires such as controlled burns (Russell et al 2009), and it also occurs to some extent in unburned forests (Dixon andSaab 2000, Tremblay et al 2009). Habitat heterogeneity, with low-severity and unburned areas interspersed with more severely burned patches, may be important in maintaining the quality of woodpecker habitat beyond the first few years post fire (Nappi et al 2010). Clearly, a better understanding of region-specific responses of Black-backed Woodpeckers to characteristics of burned forests is needed to refine their use as an indicator of conditions within recently burned forest stands.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in mean nest density in no-salvage units may be due to improvements in habitat quality over time because they contained more areas that burned at moderate severity than the other treatment types and therefore may have more ongoing tree mortality over the seven years since fire (Angers et al 2011). Newly recruited snags in these areas may have provided foraging and reproductive habitat for both woodboring beetles and Black-backed Woodpeckers (Nappi et al 2010, Dudley et al 2012. Snag densities were relatively high at nest sites both before (~194 snags/ha for small diameter snags and ~180 snags/ha for medium diameter snags) and after (~108 snags/ha for small diameter snags and ~200 snags/ha for medium diameter snags) logging.…”
Section: Discussionmentioning
confidence: 99%
“…These woodpeckers are considered specialist predators of wood-boring larva on account of morphological and behavioral adaptations that enable them to extract burrowing prey more efficiently than their competitors (Tremblay et al 2016). In recently burned forest (1-3 year-old), Black-backed woodpeckers foraged in high severity areas immediately after fire, although they preferred moderately burned snags as foraging substrate (Nappi et al 2010). In older (6-8 year-old) burns, larger snags in dense stands were selected for foraging; burn severity was not influential (Dudley et al 2012) and foraging occurred at the fire periphery and in green patches .…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the height of the vegetation immediately following the fire area would be zero, and the height of vegetation observed in 2010 would be the result of a post-fire recovery. Yet numerous studies have shown that most boreal forest fires leave a mosaic of surviving and dead standing vegetation elements within the outer perimeter of the area affected by a forest fire [18][19][20][21][22][23]. Areas registered as burned in the national Forest Fire Database [24] may include a mosaic of different starting points for the post-fire canopy recovery process.…”
Section: Introductionmentioning
confidence: 99%